2020
DOI: 10.1097/cce.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Incidence, Duration, and Severity in Critically Ill Patients With Coronavirus Disease 2019

Abstract: Objectives: To determine delirium occurrence rate, duration, and severity in patients admitted to the ICU with coronavirus disease 2019. Design: Retrospective data extraction study from March 1, 2020, to June 7, 2020. Delirium outcomes were assessed for up to the first 14 days in ICU. Setting: Two large, academic centers serving the state of Indiana. Patients: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
5
50
1
1
Order By: Relevance
“…and precipitating factors (which can be classified into 3 domains: disease severity, exposure to medications and environmental factors), it is likely that this increase in prevalence of delirium is not a product of a specific brain tropism of the virus but rather a massive burden of precipitating factors (regarding sedation, immobility, isolation, etc.). ( 81 , 83 ) The concept of eCASH proposed by Vincent et al is a good starting point for discussing nonpharmacological treatment measures. ( 54 ) Comfort as a first need, adequate analgesia, minimal sedation and humanized care focused on the patient and family are the axes of this new paradigm for intensive medicine.…”
Section: Resultsmentioning
confidence: 99%
“…and precipitating factors (which can be classified into 3 domains: disease severity, exposure to medications and environmental factors), it is likely that this increase in prevalence of delirium is not a product of a specific brain tropism of the virus but rather a massive burden of precipitating factors (regarding sedation, immobility, isolation, etc.). ( 81 , 83 ) The concept of eCASH proposed by Vincent et al is a good starting point for discussing nonpharmacological treatment measures. ( 54 ) Comfort as a first need, adequate analgesia, minimal sedation and humanized care focused on the patient and family are the axes of this new paradigm for intensive medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies that have measured delirium in COVID-19 have reported higher frequencies, mainly due to difference in patient selection (12,24) since they included only ICU patients. Severity of COVID-19, evidenced by higher NEWS2 score and the need of ICU hospitalization, is associated to higher incidence of delirium, as reported before (24). In our patients, delirium was associated with older age, as described in previous studies in critically-ill patients, either with COVID-19 (25) or in other settings (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies that have measured delirium in COVID-19 have reported higher frequencies, mainly due to difference in patient selection (12,24) since they included only ICU patients. Severity of COVID-19, evidenced by higher NEWS2 score and the need of ICU hospitalization, is associated to higher incidence of delirium, as reported before (24).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies that have measured delirium in COVID-19 have reported higher frequencies, mainly due to difference in patient selection (12,24) since they included only ICU patients. Severity of COVID-19, evidenced by higher NEWS2 score and the need of ICU hospitalization, is associated to higher incidence of delirium, as reported before (24). In our patients, delirium was associated with older age, as described in previous studies in critically-ill patients, either with COVID-19 (25) or in other settings (26,27).…”
Section: Discussionmentioning
confidence: 98%